Assessment of value added to engineering projects - Mosweu, Collen (2012)
M.Ing. === The topic of this research project is 'Assessment of value added to engineering projects'. In this dissertation the aim is to introduce the reader to the methodologies, which can be used to add value to engineering projects. Engineering has to do with the application of science in solving problems, while technology is the study or use of the mechanical arts or applied sciences. The author saw it fitting to combine value engineering principles, systems engineering, business process re-engineering, technology scanning and innovation technology management principles to base this dissertation on the research of the combined principles. The intention of this research is not to replace the current project management or processes on how to manage and create value in engineering projects. The research merely identifies an issue and proposes a process as an addition to the current processes rectifying this 'lack of value' issue.